Emotional intelligence as a component of civil services training - An exploratory study - Kaur, Gurvinder; Sharma, Vibha (2009)
Emotional Intelligence (EI) is being seen as one of the possible solutions for the chaos that afflicts polity and administration in the country, as in the rest of the world. The premise is that emotionally intelligent people make better humans and better workers, and in the long run, lead to the formation of a viable democracy. This article defines the concept of emotional intelligence and provides its scientific explanation. it throws light on the relevance of EI at Workplace especially in the context of civil services and makes a case for inclusion of EI as a component of training of civil servants. - Reproduced.
Keywords: Training; Civil service; Emotional development